Managing Adaptation to Climate Risk : Beyond Fragmented Responses. - O'Brien, Geoff (Taylor and Francis, 2013)
Climate change is the single largest threat to the attainment of the Millennium Development Goals (MDGs) and sustainable development. Addressing climate risk is a challenge for all. This book calls for greater collaboration between climate communities and disaster development communities. In discussing this, the book will evaluate the approaches used by each community to reduce the adverse effects of climate change. One area that offers some promise for bringing together these communities is through the concept of resilience. This term is increasingly used in each community to describe a pr.